Stellaria procumbens sp. nov. and S. amplexicaulis comb. & stat. nov. (Caryophyllaceae) from Southwest China - Yang, Feng; Liu, Xiao-Lan; Li, Yu-Ran; Tian, Ye; Wang, Huan-Chong (Phytotaxa, 2020)
Stellaria procumbens Huan C. Wang & Feng Yang, a new species in Caryophyllaceae, is described and illustrated. The new species was found in provinces Sichuan and Yunnan, Southwest China. Stellaria procumbens is most similar to S. longifolia, but clearly differs from the latter by its stems cylindrical, 5–10 cm in length, leaves 0.4–1.5 cm long, 0.3–0.7 mm broad, the ratio of length to width of leaves from 13 to 23, cymes usually with 1–2 (–3) flowers, and peduncles 0.3–2.5 cm long. Also, the variety S. saxatilis var. amplexicaulis from southwest China, is raised to species rank based on its distinctiveness and its lectotype is designated.